2010
DOI: 10.1093/ije/dyq027
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus toxoid immunization to reduce mortality from neonatal tetanus

Abstract: Background Neonatal tetanus remains an important and preventable cause of neonatal mortality globally. Large reductions in neonatal tetanus deaths have been reported following major increases in the coverage of tetanus toxoid immunization, yet the level of evidence for the mortality effect of tetanus toxoid immunization is surprisingly weak with only two trials considered in a Cochrane review.Objective To review the evidence for and estimate the effect on neonatal tetanus mortality of immunization with tetanus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
174
1
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(192 citation statements)
references
References 20 publications
8
174
1
5
Order By: Relevance
“…11 Two or more properly timed doses of Tetanus toxoid immunization given to pregnant woman or woman of child bearing age will reduce Neonatal Tetanus mortality by 94%. 12 Tetanus immunoglobulins are actively transported through the placenta from an immunized mother to her foetus, providing passive protection against Tetanus during Neonatal period & following month or two of life. 12 …”
Section: Keymessagesmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Two or more properly timed doses of Tetanus toxoid immunization given to pregnant woman or woman of child bearing age will reduce Neonatal Tetanus mortality by 94%. 12 Tetanus immunoglobulins are actively transported through the placenta from an immunized mother to her foetus, providing passive protection against Tetanus during Neonatal period & following month or two of life. 12 …”
Section: Keymessagesmentioning
confidence: 99%
“…12 Tetanus immunoglobulins are actively transported through the placenta from an immunized mother to her foetus, providing passive protection against Tetanus during Neonatal period & following month or two of life. 12 …”
Section: Keymessagesmentioning
confidence: 99%
“…Costs of visits were estimated to be 9% higher in regions with 80-95% coverage, and 24% higher in regions with 95-99% coverage, than were visits in regions with less than 80% coverage. Cost assumptions are detailed in webappendix pp [3][4][5][6][7][8][9][10][11][12][13][14][15] Eff ect estimates refer to the reduction in deaths due to a specifi c cause as a result of intervention-eg, 0·41 for stillbirths due to neural tube defects means that 41% of stillbirths due to neural tube defects could be averted with introduction of folic acid supplementation or fortifi cation. Postnatal interventions are not included so the estimates do not represent the full eff ect on neonatal deaths.…”
Section: Eff Ects and Cost Of Interventionsmentioning
confidence: 99%
“…The review by Lawn et al [275] reported that it can lead to significant reduction in the risk of neonatal mortality 52000 g (RR 0.49; 95% CI: 0.29 to 0.82) and severe neonatal morbidity (RR 0.34; 95% CI: 0.18 to 0.65). Moreover, KMC was also found to increase rates of breastfeeding (RR 1.20; 95% CI: 1.01 to 1.43), and mother-infant attachment (RR 6.24; 95% CI: 5.57 to 6.91) [276].…”
Section: Support and Promotion Of Early Initiation And Continued Breamentioning
confidence: 99%